(untitled) (Eurasian Journal of Philology Science and Education, 2024)
In current linguistic researches special attention is paid to the linguistic nature of the views of a native speaker on the views of an ethnocommunity on phenomena in the world through the continuity of «language-ethnicity-culture». Accordingly, the mental image that formed under the subtext of ethnocultural semantics of phraseological units created through using ornitonymic components of the Kazakh language is based on the interrelated continuity of the ethnic group’s ideas about the world of birds and the real world. The goal of the research is to perceptvarious fragments of the world picture (worldview) by considering ornitonymic phraseological units in the linguocultural and linguocognitive aspects. As for the scientific and practical significance of the research work, ornitonymic phrasemes are a lexical unit that includes such complex categories as ethnicity, worldview, culture and mentality. Since the article considers problems of such fields of science as cultural linguistics, cognitive linguistics, phraseosemantics, ethnolinguistics, it helps to replenish the theoretical base of these fields and enrich their practical content. Practical results of the research can be reasonably used in lecture materials on a particular research area within the framework of the anthropocentric paradigm, in coursework and graduate work, and in materials of independently conducted research. During the analysis of the ethnomarker image of ornitonymic phraseological units, indecomposable phrases created through the use of ornitonymic components were collected from «Phraseological Dictionaries of the Kazakh Language» (I. Kenesbaev, A. Kaidar, G. Smagulova) and they were comprehensively studied by using descriptive, comparative, explanatory methods through contextual, linguistic and cultural analysis. In this research, the special object of study is ornitonymic phraseological units that are comprehensively examined from a theoretical and practical point of view within the framework of the anthropocentric paradigm. Phrasemes formed by combining ornitonymic components play a significant role in demonstrating ethnocultural heritage in the language of the nation. In the research, the continuity of the parallel between worlds of «birds and people» is shown through the description and use of the ethnocultural meaning of ornithonym phrasemes. Value and practical significance of the research: studying ornitonymic phrases is mainly focused not only on conveying names of birds and their allegorical meanings, but also on the unity of the ethnic group that cannot be separated from the natural world. The priority of the research work is to consider the origin and formation of ornitonymic phrasemes, their cultural semantics, scope of application and semantic field in various aspects. Ornithonymic phraseology accumulates such characteristics of an ethnos as character, behavior, culture, worldview, and through linguistic units it forms an ornithonymic picture of the world in the human mind. Thus, in ornitonymic phraseological units the original national peculiarity of the ethnos and the cognitive activity of imaginative thinking are shown. Key words: ornithonym, phraseme, semantics, pragmatics, ethnicity, culture, picture of the world, poetics.